Effect of Social Media on Learning Effectiveness: Examining the mediating role ofthe Socialization, Externalization, Combination, Internalization and knowledgesharing. (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study examines the mediating role of Nonaka’s knowledge spiralsof SECI.Whetherthishasarelationshipwiththeeffectofsocialmediaonknowledgesharingandexamines whether it leads to effective learning. The effect on knowledge sharing through socialmedia which was constructed by Bock et al. (2005) has been used for measuring in this study. Themediating role of SECI on social media and knowledge sharing for effective learning has beenassessed based on the four dimensionsSECI multi-dimensional questionnaire offered by Nonakaet al. (2000) has been used for this study. The results reveal which of the four dimensions of Nonaka's that, which has a significant impact on effective learning using social media & knowledge sharing that has been brought to light from this study. The empirical findings of thisstudymayenable toenrichthetheoreticaland practicalimplications.